MODELING AND SIMULATION OF TRAFFIC FLOWS ON INCLINED ROAD DURING EVACUATION PROCESS OF THE VOLCANO DISASTER WITH FINITE DIFFERENCE METHOD - Richasanty Septima; Said Munzir; Salmawaty Salmawaty (Jurnal Natural, 2017)
The research in this thesis was done to examine the model of traffic flow of volcanic disaster evacuation path for uphill and downhill roads. The assessment was focused on the area of disaster evacuation path from the Pante Raya Bener Meriah intersection to Takengon. This model is assessed for two different types of time when which a disaster occurs; the disaster occurred at night and the disaster occurred during the day, especially during peak hours (working hours). The model was developed with attention to the exixtence of inflow and outflow along the evacuation route. Furthermore, the model obtained is solved numerically by using finite difference method. The chosen approach of this method is upwind scheme with time and space steps using forward difference and backward difference. The solution of this model in the form of simulated vehicle density along evacuation pathways. The research conducted is in the form of a model of traffic flow on evacuation paths and restricted to the inflow and outflow without alternative path as well as the conditions of the road which are uphill and downhill, showed a high density of vehicles either at night or during the day. Uphill road conditions resulted in decreased vehicle speed and vehicle density will increase, while downhill road conditions resulted in increased vehicle speed and vehicle density will decrease, meaning that the road conditions which are uphill and downhill will greatly affect the process of evacuation. Degree vehicles of evacuation efficiency occuring at night without an alternative pathway produces a high efficiency so that it can be interpreted that the evacuation process in the evening was successful and runs better than the evacuation process during the day, and this is caused by the existence of vehicles on the road  evacuation process started thus affecting the efficiency levels. Keywords : Traffic flows, finite difference method, upwind scheme method, forward difference, backward difference, greenshield method, uphill road, downhill road.